2022
DOI: 10.1038/s42005-022-00923-1
|View full text |Cite
|
Sign up to set email alerts
|

Strong bulk-surface interaction dominated in-plane anisotropy of electronic structure in GaTe

Abstract: Recently, intriguing physical properties have been unraveled in anisotropic layered semiconductors, in which the in-plane electronic band structure anisotropy often originates from the low crystallographic symmetry and thus a thickness-independent character emerges. Here, we apply high-resolution angle-resolved photoemission spectroscopy to directly image the in-plane anisotropic energy bands in monoclinic gallium telluride (GaTe). Our first-principles calculations reveal the in-plane anisotropic energy band s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…T. Okamoto et al have shown that low T S = 500 °C and VI/III ∼ 30 can apparently promote the formation of a vacancyordered Ga 2 Se 3 phase inclusions in the growing film. 20,40 In this regard, one can see that the conditions established for the MBE growth of Ga 2 Se 3 layers do not differ much from the conditions for GaSe, and the high VI/III flux ratio used for the growth of GaSe films with a Se valve cracking cell can promote the formation of Ga 2 Se 3 phase. In other words, the exact growth parameters of GaSe or Ga 2 Se 3 layers depend strongly on the setup used and require test growth processes.…”
Section: Van Der Waals Epitaxymentioning
confidence: 91%
See 2 more Smart Citations
“…T. Okamoto et al have shown that low T S = 500 °C and VI/III ∼ 30 can apparently promote the formation of a vacancyordered Ga 2 Se 3 phase inclusions in the growing film. 20,40 In this regard, one can see that the conditions established for the MBE growth of Ga 2 Se 3 layers do not differ much from the conditions for GaSe, and the high VI/III flux ratio used for the growth of GaSe films with a Se valve cracking cell can promote the formation of Ga 2 Se 3 phase. In other words, the exact growth parameters of GaSe or Ga 2 Se 3 layers depend strongly on the setup used and require test growth processes.…”
Section: Van Der Waals Epitaxymentioning
confidence: 91%
“…T. Okamoto et al have shown that low T S = 500 °C and VI/III ∼ 30 can apparently promote the formation of a vacancy-ordered Ga 2 Se 3 phase inclusions in the growing film. 20,40…”
Section: Sample Growth and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Layered GaS, GaSe and GaTe materials all exhibit large out-of-plane anisotropy in their mechanical, optical, and electrical properties, a common feature in vdW compounds. ,− ,, Uniquely, α-GaTe also displays in-plane anisotropy, which has traditionally been attributed to its asymmetric crystal structure. However, recently Lai et al claimed that strong bulk-surface interactions are the true underlying cause. Hexagonal GaSe crystals have garnered particular attention due to their nonlinear optical properties in the infrared (IR) range and their exceptional transparency between 650–18000 nm. , …”
Section: Ga Monochalcogenidesmentioning
confidence: 99%
“…За счет своих уникальных свойств материал широко используется при разработке электронных приборов и устройств оптоэлектроники. Теллурид галлия относится к слоистым полупроводникам [1], легко формируется в виде 2D структур [2][3][4][5][6], имеет энергетическую диаграмму с прямой зоной [7][8][9], может существовать в различных структурных модификациях [10][11][12][13], имеет ярко выраженную анизотропию свойств [8,[14][15][16]. Эти и другие свойства позволяют применять кристаллы, пленки и 2D структуры (nanosheets, nanoflakes) GaTe при разработке фотодетекторов и солнечных элементов [17][18], транзисторов и фототранзисторов [19][20][21], элементов электроники и фотоники [22][23][24], устройств фотокатализа [25,26], литий-ионных элементов [27] и т. д. В настоящее время наряду с активным изучением низкоразмерных 2D систем проводятся комплексные исследования по формированию и использованию 1D объектов на основе теллурида галлия.…”
Section: Introductionunclassified